2012
DOI: 10.1007/s00262-012-1337-y
|View full text |Cite
|
Sign up to set email alerts
|

Sinomenine hydrochloride enhancement of the inhibitory effects of anti-transferrin receptor antibody-dependent on the COX-2 pathway in human hepatoma cells

Abstract: Transferrin receptor (TfR) has been used as a target for the antibody-based therapy of cancer due to its higher expression in tumors relative to normal tissues. Great potential has been shown by anti-TfR antibodies combined with chemotherapeutic drugs as a possible cancer therapeutic strategy. In our study, we investigated the anti-tumor effects of anti-TfR monoclonal antibody (mAb) alone or in combination with sinomenine hydrochloride in vitro. Results suggested that anti-TfR mAb or sinomenine hydrochloride c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 25 publications
2
27
0
Order By: Relevance
“…2). Some studies have indicated that sinomenine inhibited the expression of COX-2 [30], [31]. Consistent with these results, our findings manifested that sinomenine downregulated COX-2 expression in MDR-caco-2 cells (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…2). Some studies have indicated that sinomenine inhibited the expression of COX-2 [30], [31]. Consistent with these results, our findings manifested that sinomenine downregulated COX-2 expression in MDR-caco-2 cells (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…Cell lysates were centrifuged at 12000 rpm for 5 min and the supernatants were divided on 12% polyacrylamide gel. The transferred membrane was immunoblotted with mouse anti-hTfR monoclonal antibody (anti-hTfR mAb, produced by our laboratory [ 6 8 ]) overnight at 4°C followed by HRP-labeled goat anti mouse Ab (Southern Biotech, Birmingham, USA) for 1h at 37°C. Proteins were detected using ECL kit (Pierce, Rockford, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Iron overload conditions contribute to several pathological conditions including iron overload-related hepatic cancer [24]. The TfR expression level is often higher in the tumor tissue than the normal tissue [20]. Therefore, Tf can be used as the ligand for targeting liver tumor.…”
Section: Resultsmentioning
confidence: 99%
“…Transferrin (Tf) is one of the most widely used tumor-targeted ligands because Tf receptors (TfRs) are over-expressed on malignant cells and play a key role in cellular iron uptake through the interaction with Tf [17]. Moreover, the expression level of TfRs has been suggested to correlate with tumor stage or cancer progression [18-20]. …”
Section: Introductionmentioning
confidence: 99%